Pengaruh Kompetensi , Indepedensi, Akuntabilitas, dan Due Profesional Care Pada Kualitas Audit - Alam, Darsyaf Icap; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 21 No 3 (2017)DO - 10.24843/EJA.2017.v21.i03.p21, 2017)
Trust users of audited financial statements and public accounting services require the public accounting firm to pay attention to audit quality. Audit. Users of financial statements argue that the quality of the audit in question occurs if the auditor can provide assurance that there is no material misstatement or fraud in the financial statements. This study aims to analyze and obtain empirical evidence on the influence of independence, competence, due professional care, and auditor accountability to audit auditor quality Public Accounting Firm in Bali Province. The population in this study is all auditors who work at Public Accounting Firm in Bali Province. Sample determination method used in this research is saturated sample method. Data collection used in this study is by using questionnaires by distributing questionnaires to 40 auditors who became respondents. Data analysis was done by multiple linear regression method. Based on the results of the analysis has been found partially that the variables of competence, independence, accountability, and professional care has a positive and significant impact on audit quality.